1997
DOI: 10.1039/a701856h
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer characterisation of gold/iron oxide catalysts

Abstract: 57Fe and 197Au Mo ssbauer data have been reported and discussed for a variety of catalysts of gold supported on iron oxide. The 57Fe Mo ssbauer spectra show that iron is present as ferrihydrite, haematite and goethite in amounts that depend on the conditions of preparation. The highest amount of ferrihydrite is observed in the samples prepared by coprecipitation. The 197Au Mo ssbauer spectra reveal the formation of two main gold species, i.e., metallic gold and oxidic trivalent gold. The presence of gold favou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 6 publications
7
57
0
Order By: Relevance
“…It is unlikely that oxidic Au species are the major catalytically active phases because the most active supported Au catalysts are prepared by calcination in air at 573K, where Au precursors (hydroxides or organo complexes) are mostly transformed into metallic particles. A certain fraction of Au species remain as atomically dispersed species in the matrix of the support, as proved by EXAFS (8,50,53,54), XPS (51), Mössbauer (52,55), and IR of CO adsorbed (43,49).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that oxidic Au species are the major catalytically active phases because the most active supported Au catalysts are prepared by calcination in air at 573K, where Au precursors (hydroxides or organo complexes) are mostly transformed into metallic particles. A certain fraction of Au species remain as atomically dispersed species in the matrix of the support, as proved by EXAFS (8,50,53,54), XPS (51), Mössbauer (52,55), and IR of CO adsorbed (43,49).…”
Section: Figurementioning
confidence: 99%
“…The data for Pt group metals are taken from ref. [41] (51,52). It is unlikely that oxidic Au species are the major catalytically active phases because the most active supported Au catalysts are prepared by calcination in air at 573K, where Au precursors (hydroxides or organo complexes) are mostly transformed into metallic particles.…”
Section: Figurementioning
confidence: 99%
“…A detailed characterisation by 197 Au and 57 Fe Mossbauer spectroscopy and XPS spectroscopy of gold catalysts prepared by coprecipitation (entries 2-9) have revealed that gold is present as Au(III) and Au (metal) and the support is a mixture of ferrihydrite, and hematite [25,27], The amount of ferrihydrite on such catalysts has been found to increase with the gold loading. XRD analysis have shown that all the samples, but AF046/b, are amorphous [28].…”
Section: Resultsmentioning
confidence: 99%
“…However, gold in a higher oxidation state has been also shown to chemisorb carbon monoxide [37]. 197 Au Mossbauer spectroscopy [25] and XPS spectroscopy [26], have revealed that when the catalysts are not calcined at high temperature (as in the case of the catalysts reported in this paper) gold is mainly present as Au(III).…”
Section: Selective Oxidation Of O-hydroxybenzylalcoholmentioning
confidence: 98%
“…An increase in the temperature to 600 K provides a higher O/Au ratio (up to 2). The presence of trivalent gold in the Au/MeO x catalysts was detected by 197 Au Mössbauer spectroscopy (45,46), XPS (37,47), and XANES (37). Different hydroxylated species of gold, such as Au(OH) 3 (37) and AuO(OH) · H 2 O (46), were also found.…”
Section: Effect Of Pretreatmentmentioning
confidence: 99%